Productivity of the Czech Republic Measurement at Aggregate and Economy Level Growth of Productivity and Classification of Enterprises - Jangra, Sandeep (2022)
The aim of the work I selected this master thesis to work on massive amount of data provided by the Czech Statistical Office (CZSO) and TFP has gained importance as it has been helpful in accelerating the rate of economic growth. Keeping this in mind I identified the importance of having correct measure of productivity for the growth of enterprises, along with list of determinants. I would like to thank Professor Jan Fisher who explained me about the topic. Many researchers had published their research work using multiple methodologies and various inputs, so I would like to contribute my work in identifying productivity of the Czech Republic enterprises with two key determinants. From there my journey to know about TFP started and with my work, I wanted to correctly estimate the productivity growth of the Czech Republic. Lots of complication and concerns were raised and I knew it before taking this thesis, but I kept myself focused on providing nearest correct figures while addressing concerns raised by multiple people. This thesis sets out examine the TFP of the Czech Republic enterprises and its determinants., rather than on output growth. I carefully considered the theoretical links between TFP and two input factors (capital and labour) and one output factor (revenue/value added). Another interesting task assigned along with this topic was to identify incorrectness of data. Although not much work has been done in this direction during implementation but still to a certain point it has been achieved. I also maintained cleanliness of data and reported them to my point of contact in Czech Statistical Office. I aimed to provide relevant theoretical background of total factor productivity growth of enterprises while limiting my thesis to only two factor of inputs – labour and capital. Also, I investigated and tried to find out what are all sectors in the Czech Republic whose productivity, although, decreasing but how deep it dwindles.